Sistem Informasi Calon Penerima Beasiswa Menggunakan Algoritma Cart Decision Tree Pada SMA Kristen Gollu Watu - Detami, firmina; Umar, Elfira; Ate, Paulus Mikku (Prodi Sistem Informasi Universitas Dharma Andalas, 2024)
SMA Kristen Gollu Watu It's an institution of education that has two majors in science and social science..The method of decision tree is a supporting tool with a treelike structure that models possible outcomes, cost, resource, utility, and possible consequences.Decision tree or tree decision because of its branching options, form a structure that looks like a tree.As for the purpose of research, it is to understand and understand the use and operation of the method of decision tree for decision-making scholarship admissions that can help the school to accept scholarships in order to be on target.